Pengaruh Pengembangan Karir, Pelatihan Kerja, Stres Kerja, dan Lingkungan Kerja Fisik Terhadap Kinerja Pegawai Puskesmas Tegal Timur - Tofani, Amelina Rosada Nur; Hanfan, Ahmad; Cahyaningtyas, Niken Wahyu (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
The purpose of this research is to examine the impact on productivity of factors such as professional growth opportunities, on-the-job training, occupational stress, and the physical work environment as they pertain to the staff at the Tegal Timur Community Health Center. Quantitative research methods were employed with data collected from the Tegal Timur Community Health Center as the subject of study. A sample size of 52 respondents was used. The method of sampling was based on random sampling. We used a questionnaire to gather our data. Using SPSS 22, we conducted analyses using descriptive statistics and multivariate structural integration (MSI). Employee Performance at the Tegal Timur Community Health Center was found to be positively and significantly impacted by Career Development, Job Training, Work Stress, and Physical Work Environment.